A Bore-sight Motion Detection Algorithm for Satellite Attitude Control - Visagie, Lourens (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.